Case Report: [18F]PI2620 as a Tau Imaging Agent in Posterior Cortical Atrophy - Kong, Yu; Xie, Kexin; Qiao, Hongwen; Cui, Yue; Jing, Donglai; Wang, Yuting; Li, Xuying; Wu, Liyong (Frontiers in Neurology, 2020)
Posterior cortical atrophy (PCA) is widely considered as an atypical variant of Alzheimer disease and is characterized by a progressive decline in visual function. PCA has been investigated from the standpoints of brain structure and metabolism, but tau deposition and its relationship to disease severity still remain unclear. Here, we used a novel tau ligand, [18F]PI2620, to visualize tau deposition in a PCA patient. The results showed that high [18F]PI2620 uptake in posterior cortical regions was associated with clinical manifestations, morphologic changes in the brain observed by magnetic resonance imaging (MRI), and hypometabolism detected by [18F] fluorodeoxyglucose (FDG) positron emission tomography (PET). This is the first report demonstrating a clinical anatomical correspondence between [18F]PI2620 PET results, clinical manifestations, MRI, and [18F]FDG PET findings in a Chinese patient with PCA. The results also support the utility of [18F]PI2620 for visualizing tau aggregation in PCA.